1973
DOI: 10.1037/h0082351
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality of internal-external control: Implications for past and future research.

Abstract: Factor analyzed the scores of 130 20-55 yr old females in a weight-reducing club and 85 undergraduates on Rotter's Internal-External Control Scale. Results of the 2 studies offer rather clear evidence that there are at least 2 independent factors of Internal vs External (I-E) control. The 1st factor, "Fatalism," concerned the belief that luck, fate, or fortune vs hard work, ability, and personal responsibility determine one's outcomes. The 2nd factor, "Social System Control," measured the extent to which peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 11 publications
1
37
0
2
Order By: Relevance
“…In response to the growmg number of Studies which report that Rotter's I-E scale is not homogeneous, the current study was conducted using only the personal control factor, which consists of 18 of the original 23 items It is noteworthy that when the full I-E scale was used the results, while in the same direction, diminished in magmtude. In effect, the social system control factor proved to be a "noisy variable" la predicting this highly personal cnterion This finding lends support to critics such as Reid and Ware (1973) who have suggested a multiple regression approach to the use of these two factors of I-E Secondly, the results with Crandall's IAR raise some interesting questions. Very few investigators have explored the relationship between the IAR and the I-E scales largely because the former is thought to be solely for children, the latter for adults While children would no doubt fail to understand many items of the I-E scale, adults would not often misunderstand the IAR.…”
Section: Josupporting
confidence: 53%
“…In response to the growmg number of Studies which report that Rotter's I-E scale is not homogeneous, the current study was conducted using only the personal control factor, which consists of 18 of the original 23 items It is noteworthy that when the full I-E scale was used the results, while in the same direction, diminished in magmtude. In effect, the social system control factor proved to be a "noisy variable" la predicting this highly personal cnterion This finding lends support to critics such as Reid and Ware (1973) who have suggested a multiple regression approach to the use of these two factors of I-E Secondly, the results with Crandall's IAR raise some interesting questions. Very few investigators have explored the relationship between the IAR and the I-E scales largely because the former is thought to be solely for children, the latter for adults While children would no doubt fail to understand many items of the I-E scale, adults would not often misunderstand the IAR.…”
Section: Josupporting
confidence: 53%
“…Using Reid and Ware's (1974) Internal±External locus of control scale, Hood et al (1982) compared scores of female anorexic patients (n=54) to scores derived fromÐBeck Depression Scale, Body Image, Eating Attitudes Test (EAT), Eysenck Personality Questionnaire (EPQ), Sixteen Personality-Factor Questionnaire (16PF), and the Restraint Scale. Findings revealed that younger anorexic patients (mean age=16.3 years) demonstrated higher internal control compared to published norms on the various questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…At initial testing, only self-report data were avail able including weight, vomiting frequency, menstrual status and the following standardized tests: (1) Eating Disorder Inventory (EDI) [Garner and Olmsted, 1984], (2) Family Assessment Measure (FAM) [Skin ner et al, 1983], (3) Locus of Control [Reid and Ware, 1973] and (4) Feelings of Inadequacy [Janis and Field. 1959], At follow-up testing, subjects were administered the EDI and a demographics form and those whose weight, weight history, menstrual status or EDI re sults were suggestive of an eating disorder were inter viewed by a psychiatrist to determine the presence of anorexia nervosa (AN, DSM-III) [American Psychiat ric Association, 1980], bulimia nervosa (BN) [Russell, 1979] or 'partial syndrome' (PS) [Szmukler, 1983].…”
Section: Methodsmentioning
confidence: 99%